1988
DOI: 10.1128/mcb.8.6.2555
|View full text |Cite
|
Sign up to set email alerts
|

A discrete element 3' of human immunodeficiency virus 1 (HIV-1) and HIV-2 mRNA initiation sites mediates transcriptional activation by an HIV trans activator.

Abstract: An important point of regulation in the reproductive growth and latency of the human and simian immunodeficiency viruses (HIV and SIV, respectively) is provided by virally encoded trans-activators (tat), proteins capable of dramaticaily increasing viral gene expression. The mechanism of this autostimulatory pathway has remained unclear, however, with substantial effects having been reported at the level of either niRNA accumulation, translational efficiency, or both. Our previous findings indicated that trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
221
1
3

Year Published

1989
1989
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(233 citation statements)
references
References 34 publications
8
221
1
3
Order By: Relevance
“…RNAs were 5Ј end-labeled with 0.5 M [␥- 32 P]ATP [6,000 Ci͞ mmol (1 Ci ϭ 37 GBq), ICN] per 100 pmol of nucleic acid by incubation with 16 units of T4 polynucleotide kinase (NEB, Beverly, MA) in the provided buffer. 5Ј end-labeled RNAs were purified on a 20% denaturing gel, visualized by autoradiography, eluted from the polyacrylamide gels, and desalted on a reversephase cartridge.…”
Section: Methodsmentioning
confidence: 99%
“…RNAs were 5Ј end-labeled with 0.5 M [␥- 32 P]ATP [6,000 Ci͞ mmol (1 Ci ϭ 37 GBq), ICN] per 100 pmol of nucleic acid by incubation with 16 units of T4 polynucleotide kinase (NEB, Beverly, MA) in the provided buffer. 5Ј end-labeled RNAs were purified on a 20% denaturing gel, visualized by autoradiography, eluted from the polyacrylamide gels, and desalted on a reversephase cartridge.…”
Section: Methodsmentioning
confidence: 99%
“…Upon binding the regulatory protein Tat and the host cellular proteins cyclin T and CDK9, the TAR hairpin stabilizes RNA polymerase II to allow viral transcription (1)(2)(3)(4)(5)(6). Only the apical portion of the stem loop from positions ϩ19 to ϩ42 is required for transcriptional activation in vivo (7). Extensive mutagenesis studies have shown that the region of TAR important for binding Tat involves a set of nucleotides that surround a characteristic UCU nucleotide bulge; important residues include U23, the first bulged nucleotide, and the two base pairs that immediately precede and follow the bulge (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The Tat/TAR interaction may have functional consequences at both the transcriptional (8,9) and posttranscriptional levels (10,11). At the transcriptional level, Tat has been shown to enhance or stabilize binding of transcription complexes required for efficient initiation and elongation of viral RNAs (12,13).…”
mentioning
confidence: 99%